(3GdOQ GdefXhe ef faGFS GdYdhes
(3ChdgG (B:s
(3GdMeO ddg GdehLhO GdeMehO Hcd dSGf s
(3BNQgG (B:s
(3hGdMeO ddg Ydi GdJeGe s
(3Vef eLehY , JQJjHgG (B: 2s
(3GdfSNI HgG MhGTs
(3hQO ai EjVGM Gdecfhf(B: (3GdOQ GdefXhe dCgd GdYdhes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B452s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs